2017
DOI: 10.1007/s40710-016-0206-7
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Cu, Zn and Mn in an Intensive Fish Aquaculture (Tilapia - Oreochromis niloticus) in an Artificial Reservoir in Northeastern Brazil

Abstract: Emissions of Cu, Zn and Mn and their fate in a typical tilapia (Oreochromis niloticus) cage farm in an artificial reservoir in northeastern Brazil were estimated through the analysis of their concentrations in the various compartments of the farm. Major source of Cu and Zn, but not of Mn, to the farm is from aquafeeds, with annual inputs of 3.83, 57.50 and 10.95 kg.ha −1 , respectively. Notwithstanding, only a small fraction of the added Mn and Zn (0.13%, 2.61%, respectively) is incorporated into fish biomass,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Upon reaching the shore, currents loop back into the reservoir, washing out through the bottom and export effluents from fish cages to depths below the thermocline, accumulating nutrients in the hypolimnion and keeping most of the water column oligotrophic. Details on this hydrodynamic pattern can be seen in Oliveira et al (2015Oliveira et al ( , 2017. This is facilitated by the dynamic of aquafeed pellets, which floats long enough to be transported prior to sedimentation, as demonstrated by Molisani et al (2015).…”
Section: The Impact Of Fish Farmingmentioning
confidence: 98%
“…Upon reaching the shore, currents loop back into the reservoir, washing out through the bottom and export effluents from fish cages to depths below the thermocline, accumulating nutrients in the hypolimnion and keeping most of the water column oligotrophic. Details on this hydrodynamic pattern can be seen in Oliveira et al (2015Oliveira et al ( , 2017. This is facilitated by the dynamic of aquafeed pellets, which floats long enough to be transported prior to sedimentation, as demonstrated by Molisani et al (2015).…”
Section: The Impact Of Fish Farmingmentioning
confidence: 98%
“…Oliveira et al [ 19 ] analyzed fish, sediment and fish feed in the Castanhão reservoir, semiarid region of Brazil, and observed that only 0.13% of Mn and 2.61% of Zn are incorporated by cultivated tilapia, that Cu absorption is 47.4% and that the excess percentage of these metals are sedimented and/or dispersed to other areas of the environment. The results pointed out by Oliveira et al [ 19 ] are indicators of the concentrations and dispersion of trace metals verified in the Rosário reservoir, occurring between the fish farming area (CTV) and the postculture area (PCTV).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the increase verified during the cultivation period in the Rosário reservoir, we can estimate the possibility of the future accumulation of residual metals from fish farming according to Oliveira et al [ 19 ]. For these authors, the technological package of tilapia production in the semiarid region of Brazil is predominantly standardized both in terms of cultivation management and the quality of the feed for tilapia cultivation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations